World Health Organization Estimates of the Global and Regional Disease Burden of 11 Foodborne Parasitic Diseases, 2010: A Data Synthesis. - Paul R Torgerson; Brecht Devleesschauwer; Nicolas Praet; Niko Speybroeck; Arve Lee Willingham; Fumiko Kasuga; Mohammad B Rokni; Xiao-Nong Zhou; Eric M Fèvre; Banchob Sripa; Neyla Gargouri; Thomas Fürst; et al. (PLoS Medicine)
Background Foodborne diseases are globally important, resulting in considerable morbidity and mortality. Parasitic diseases often result in high burdens of disease in low and middle income countries and are frequently transmitted to humans via contaminated food. This study presents the first estimates of the global and regional human disease burden of 10 helminth diseases and toxoplasmosis that may be attributed to contaminated food. Methods and findings Data were abstracted from 16 systematic reviews or similar studies published between 2010 and 2015; from 5 disease data bases accessed in 2015; and from 79 reports, 73 of which have been published since 2000, 4 published between 1995 and 2000 and 2 published in 1986 and 1981. These included reports from national surveillance systems, journal articles, and national estimates of foodborne diseases. These data were used to estimate the number of infections, sequelae, deaths, and Disability Adjusted Life Years (DALYs), by age and region for 2010. These parasitic diseases, resulted in 48.4 million cases (95% Uncertainty intervals [UI] of 43.4-79.0 million) and 59,724 (95% UI 48,017-83,616) deaths annually resulting in 8.78 million (95% UI 7.62-12.51 million) DALYs. We estimated that 48% (95% UI 38%-56%) of cases of these parasitic diseases were foodborne, resulting in 76% (95% UI 65%-81%) of the DALYs attributable to these diseases. Overall, foodborne parasitic disease, excluding enteric protozoa, caused an estimated 23.2 million (95% UI 18.2-38.1 million) cases and 45,927 (95% UI 34,763-59,933) deaths annually resulting in an estimated 6.64 million (95% UI 5.61-8.41 million) DALYs. Foodborne Ascaris infection (12.3 million cases, 95% UI 8.29-22.0 million) and foodborne toxoplasmosis (10.3 million cases, 95% UI 7.40-14.9 million) were the most common foodborne parasitic diseases. Human cysticercosis with 2.78 million DALYs (95% UI 2.14-3.61 million), foodborne trematodosis with 2.02 million DALYs (95% UI 1.65-2.48 million) and foodborne toxoplasmosis with 825,000 DALYs (95% UI 561,000-1.26 million) resulted in the highest burdens in terms of DALYs, mainly due to years lived with disability. Foodborne enteric protozoa, reported elsewhere, resulted in an additional 67.2 million illnesses or 492,000 DALYs. Major limitations of our study include often substantial data gaps that had to be filled by imputation and suffer from the uncertainties that surround such models. Due to resource limitations it was also not possible to consider all potentially foodborne parasites (for example Trypanosoma cruzi). Conclusions Parasites are frequently transmitted to humans through contaminated food. These estimates represent an important step forward in understanding the impact of foodborne diseases globally and regionally. The disease burden due to most foodborne parasites is highly focal and results in significant morbidity and mortality among vulnerable populations.